2021
DOI: 10.3390/ijerph181910528
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Inequalities in Access to Drinking Water among Inhabitants of Informal Settlements in South Africa

Abstract: While evidence from several developing countries suggests the existence of socio-economic inequalities in the access to safe drinking water, a limited number of studies have been conducted on this topic in informal settlements. This study assessed socio-economic inequalities in the use of drinking water among inhabitants of informal settlements in South Africa. The study used data from “The baseline study for future impact evaluation for informal settlements targeted for upgrading in South Africa.” Households … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This housing condition is an indicator of the low socio-economic status of older persons who were probably, limited in terms of resources, to help them afford sufficient energy for boiling of water, or, treating it using any other appropriate technology such as chlorination. This finding is in consonance with a study done in South Africa [64], which found that unsafely managed drinking water is associated with people's socio-economic status in slums. Similarly, a study done in Kenya [65] shows quality water for drinking is determined by an individual's socio-economic status.…”
Section: Plos Onesupporting
confidence: 91%
“…This housing condition is an indicator of the low socio-economic status of older persons who were probably, limited in terms of resources, to help them afford sufficient energy for boiling of water, or, treating it using any other appropriate technology such as chlorination. This finding is in consonance with a study done in South Africa [64], which found that unsafely managed drinking water is associated with people's socio-economic status in slums. Similarly, a study done in Kenya [65] shows quality water for drinking is determined by an individual's socio-economic status.…”
Section: Plos Onesupporting
confidence: 91%
“…An estimated 60% of Kisumu inhabitants live in informal settlements, where they face deficiencies such as a lack of access to services such as clean water and good sanitation [38]. The environment harbours resources such as groundwater, which serves as a complement to intermittent water supply for residential use, and it is critical that initiatives aimed at educating people living in informal settlements about the dangers of consuming unclean water are implemented [58]. As a result of knowing the HIV burden in the study region, knowing it follows that protecting the environment from antibiotic contamination is a key step in promoting human well-being in the one health setting.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, 93% of the population has access to water supply services and 76% have access to basic sanitation. However, the proportion of the population using improved water sources remains substantially lower in rural than in urban areas (Oskam et al, 2021 ). This clearly indicates that there is a wide disparity between urban and rural communities with respect to safe drinking water supply.…”
Section: Theoretical and Empirical Literaturementioning
confidence: 99%
“…The topography, logistics, funding, and capacity constraints account for inequity in water and sanitation services in these municipalities (Hemson, 2016 ). Decades of neglect by duty bearers and low investments in water and sanitation facilities have resulted in a mismatch between facility access and population increase, and thus, outstretched service delivery beyond sustainability levels (Oskam et al, 2021 ). The adverse impacts account for low water access and facility maintenance by the municipalities.…”
Section: Introductionmentioning
confidence: 99%